Jousting with dragons: A resilience engineering approach to managing SMS in the transport sector - Eric Arne Lofquist (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
System resilience is the ability for complex, dynamic-adaptive socio-technical systems to absorb and rebound from trauma or stress, and to avoid "jousting with dragons" where results are uncertain and often fatal. In a safety context, the term "dragons" originates from Professor David Woods at Ohio State University and the relatively new field of Resilience Engineering. Dragons are an illustration for the consequence of "surprise" as depicted in ancient seafarer maps that filled the seas beyond the known boundaries of the ancient world with fire-breathing dragons, and certain death. In a modern day sense, dragons represent the unintended, and often unforeseen and unpredictable, consequences of crossing operational boundaries that are difficult to identify precisely, are often influenced by various actors, and are continually changing. In particular, due to the complex, dynamic-adaptive behaviour of systems, classic statistical metrics used in current Safety Management Systems (SMS) no longer allow us to predict the next undesired event. We need to change our focus and find new ways of capturing the faint signals of impending failure. This will require structural, psychological and social changes in the way SMSs work. In this paper, I will address the issues of understanding and managing complex, dynamic-adaptive systems through the quality of resilience, and how to avoid "jousting with dragons" in the transport sector using a Resilience Engineering lens.
Keywords: 330; Verkehrssektor; Verkehrssicherheit; Arbeitsschutz; Risikomanagement; Unternehmenskultur; Coping-Strategie; Dynamisches System